Cost-utility analysis of the fixed-dose combination of dolutegravir/abacavir/lamivudine as initial treatment of HIV+ patients in Spain - Santiago Moreno Guillén (Farmacia Hospitalaria, 2017)
Objective: Fixed-dose combinations of antiretroviral drugs have meant an important step forward in simplifying treatment and improving com-pliance and has led to an increased effectiveness of therapy, a viral load decrease and improving the quality of life of patients.The single-table formulation of dolutegravir with abacavir and lamivudine (DTG/ABC/3TC) is a highly efficacious and well -tolerated once-daily re-gimen for HIV-infected patients. The objective of the study was to assess the incremental cost-utility ratio of the fixed-dose combination of (DTG/ ABC/3TC) versus the combinations emtricitabine/tenofovir/efavirenz (FTC/TDF/EFV), and darunavir/r (DRV/r) or raltegravir (RAL) with emtrici-tabine/tenofovir (FTC/TDF) or abacavir/lamivudine (ABC/3TC) as initial antiretroviral therapy in patients infected with HIV-1 from the perspective of the Spanish National Health System.Method: The ARAMIS model, which uses a microsimulation approach to simulate the individual changes in each patient from the start of treatment to death through a Markov chain of descriptive health states of the disease, was adapted to Spain. The alternatives used for comparison were the fixed- dose combination of emtricitabine/tenofovir/efavirenz (FTC/TDF/ EFV), and the fixed-dose combinations of emtricitabine/tenofovir (FTC/ TDF) or abacavir/lamivudine (ABC/3TC) with darunavir/r (DRV/r) or ral-tegravir (RAL). The probability of achieving virological suppression by the treatments included in the model was obtained from clinical trials SINGLE, SPRING-2 and FLAMINGO and the costs were expressed in € (2015). The model use the perspective of the Spanish National Health System, with a lifetime horizon and a discount rate of 3% was applied to cost and effectiveness.Results: Treatment initiation with DTG/ABC/3TC was dominant when it was compared with treatment initiation with all the comparators: vs. FTC/TDF/EFV (-67 210.71€/QALY), vs. DRV/r + FTC/TDF or ABC/3TC (-1 787 341.44€/QALY), and vs. RAL + FTC/TDF or ABC/3TC (-1 005 117.13€/QALY). All the sensitivity analyses performed showed the consistency of these findings.Conclusions: With the premises considered, treatment initiation with DTG/ABC/3TC STR appears to be the most cost-effective option in ART-naïve HIV infected patients from the Spanish Health System perspective.